Modern control systems - Dorf, Richard C. 1933-2020; Bishop, Robert H. 1957- (Pearson, 2022)
For courses in Control Theory. Progressively develop students' problem-solving skills through an integrated design and analysis approach to real-world engineering problems Modern Control Systems presents the structure of feedback control theory and provides a sequence of exciting discoveries as students proceed through the text and problems. Written to be equally useful for all engineering disciplines, this text is organized around the concepts of control systems theory in the context of frequency and time domains. It provides coverage of both classical and modern methods of control engineerin